Experimental Study of a Broadband Vibration Energy Harvester Based on Orthogonal Magnetically Coupled Double Cantilever Beam - Yanhao Feng; Jianhua Wang; Xiangye Chen; Peng Liu (Micromachines, 2025)
Purpose: The aim of this study is to achieve automated energy capture and charging for the ADXL355 accelerometer, enhance the vibration energy collection efficiency, and widen the energy trapping frequency band of a system in a working environment for bridge health state detection. Methods: A vibration energy harvester based on a magnetic coupling cantilever beam in an orthogonal direction was proposed. The harvester works by adjusting the angle and magnetic spacing between the two cantilever-beam piezoelectric oscillators, enabling the oscillators to produce large-scale and stable vibrations when excited by an external broadband vibration source. Results: Sinusoidal frequency sweep experiments showed that, under an excitation amplitude of 0.2 g, the proposed broadband vibration energy harvester based on orthogonal magnetic coupling double cantilever beams achieved the best energy harvesting performance when the magnetic angle of the double cantilever beam system was 130°, and the radius was 16 mm. In the frequency range of 5–20 Hz, the system can effectively capture higher effective voltages across all frequency bands, with a total captured voltage value of approximately 15.3 V. Compared with the control group, the system’s energy harvesting capacity under this working condition increases by 770%. Additionally, the effective frequency band of the system was broadened by 3.7 Hz. Conclusions: Unlike previous studies, which often limited the angles of the magnetic fields generated by the magnets at the ends of piezoelectric beams to specific values, this study explores the influence of rotating these magnetic fields to general angles on the working frequency band of the structure. The findings provide a new perspective and theoretical basis for the optimal design of broadband vibration energy harvesters.